2007
DOI: 10.1017/s0959774307000224
|View full text |Cite
|
Sign up to set email alerts
|

Depicting the Dead: Commemoration Through Cists, Cairns and Symbols in Early Medieval Britain

Abstract: This article develops recent interpretations of mortuary practices as contexts for producing social memory and personhood to argue that early medieval cairns and mounds served to commemorate concepts of gender and genealogy. Commemorative strategies are identified in the composite character, shape and location of cairns and in their relationship with other commemorative monuments, namely Class I symbol-stones. The argument is developed through a consideration of the excavations of early medieval cists and cai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…130 Similar arguments regarding the use of burial architecture to underline particular familial relations and the establishment of lineage have been made for other Pictish and early medieval cemeteries more generally. At Lundin Links, Fife, Howard Williams has suggested that the acts of containing multiple dead within single monuments and the linking of particular monuments through new acts of building created genealogies through architecture : Williams 2007. Maldonado (2013 has also suggested that cemeteries in general continually reforged relationships between the living and the dead, perhaps even creating a form of distributed personhood where the dead were considered an active part of living society.…”
mentioning
confidence: 99%
“…130 Similar arguments regarding the use of burial architecture to underline particular familial relations and the establishment of lineage have been made for other Pictish and early medieval cemeteries more generally. At Lundin Links, Fife, Howard Williams has suggested that the acts of containing multiple dead within single monuments and the linking of particular monuments through new acts of building created genealogies through architecture : Williams 2007. Maldonado (2013 has also suggested that cemeteries in general continually reforged relationships between the living and the dead, perhaps even creating a form of distributed personhood where the dead were considered an active part of living society.…”
mentioning
confidence: 99%
“…highlighted several examples of Class I (fifth-to seventh-century AD) Pictish symbol stones with multiple sets of symbols, sometimes overwriting existing symbol motifs. In both these cases, these were stones that can be raised, moved and reactivated through a series of stages in their early medieval life-histories (see also Williams 2007;Gondek, this vol. ).…”
Section: Biographymentioning
confidence: 99%